Intrapancreatic Ganglia and Neural Regulation of Pancreatic Endocrine Secretion - Li, Wenjing; Yu, Guangjiao; Liu, Yudan; Sha, Lei (Frontiers in Neuroscience, 2019)
Extrapancreatic nerves project to islet directly or converage on intrapancreatic ganglia. Intrapancreatic ganglia are innervated by sympathetic, parasympathetic, enteric, sensory nerve fibers and other intrapancreatic ganglia. Neurotransmitters of intrapancreatic ganglia and external nerves modulate the islet secretion altogether. Electrical properties of pancreatic neurons and pancreatic ganglionic transmission can affect the pancreatic endocrinal secretion. Both intrapancreatic ganglia and extrapancreatic nerves have an important influence on pancreatic endocrinal functions. This review summarize the effects of intrapancreatic ganglia and extrapancreatic nerves on endocrinal functions, but further researches are needed to clarify the roles and the mechanisms of intrapancreatic ganglia in physiological and disease states of pancreas, which may provide new approaches to treat pancreas diseases.